The Impact of Teamwork Towards Employees’ Performance in Finance Department at The Ritz-Carlton Bali - Mico Lierence; Devia Febrina; Tina Linda (Brilliant International Journal Of Management And Tourism, 2025)
Hospitality industry is one of the largest industries in the world that delivers service to guests and continuously relies heavily on its human resources in order to deliver the best service and experience for guests. To have all tasks and assignments finished without any error, such as human error or system error, teamwork is needed so that the team could anticipate any obstacles against their work lines. The purpose of doing this research is to know whether there is any impact of Teamwork towards Employees’ Performance in Finance department at The Ritz-Carlton Bali. The indicators of Teamwork are management, social cooperation, work commitment, and evaluation. And the indicators of Employees’ Performance are productivity, quality of work, and time management. The population in this research consists of all employees in Finance department at The Ritz-Carlton Bali, therefore, the amount of sample in this research is 29 staffs. The sampling method used in this research is census sampling. Based on the hypothesis results, it can be seen that Teamwork has impact on Employees’ Performance in Finance department at The Ritz-Carlton Bali and also it has a positive and strong relationship with Employees’ Performance based on correlation coefficient test. After conducting research and data analysis, the writer provided some recommendations based on the conclusion that might be helpful for the company to solve the problem